Genome engineering via homologous recombination in mouse embryonic stem (ES) cells: an amazingly versatile tool for the study of mammalian biology - CHARLES BABINET; MICHEL COHEN-TANNOUDJI (Anais da Academia Brasileira de Ciências, 2001)
The ability to introduce genetic modifications in the germ line of complex organisms has been a long-standing goal of those who study developmental biology. In this regard, the mouse, a favorite model for the study of the mammals, is unique: indeed not only is it possible since the late seventies, to add genes to the mouse genome like in several other complex organisms but also to perform gene replacement and modification. This has been made possible via two technological breakthroughs: 1) the isolation and culture of embryonic stem cells (ES), which have the unique ability to colonize all the tissues of an host embryo including its germ line; 2) the development of methods allowing homologous recombination between an incoming DNA and its cognate chromosomal sequence (gene ''targeting''). As a result, it has become possible to create mice bearing null mutations in any cloned gene (knock-out mice). Such a possibility has revolutionized the genetic approach of almost all aspects of the biology of the mouse. In recent years, the scope of gene targeting has been widened even more, due to the refinement of the knock-out technology: other types of genetic modifications may now be created, including subtle mutations (point mutations, micro deletions or insertions, etc.) and chromosomal rearrangements such as large deletions, duplications and translocations. Finally, methods have been devised which permit the creation of conditional mutations, allowing the study of gene function throughout the life of an animal, when gene inactivation entails embryonic lethality. In this paper, we present an overview of the methods and scenarios used for the programmed modification of mouse genome, and we underline their enormous interest for the study of mammalian biology. A capacidade de introduzir modificações genéticas na linhagem germinal de organismos complexos tem sido, por muito tempo, uma meta dos estudiosos da biologia do desenvolvimento. Neste aspecto, o camundongo, um modelo favorito de estudo dos mamíferos, é singular. Assim, desde o final dos anos setenta, tem sido possível não só adicionar genes ao genoma do camundongo, como em vários outros organismos complexos, mas, também realizar a substituição e modificação de seus genes. Isto tem sido possível graças a dois rasgos tecnológicos: 1) o isolamento e cultura de células-tronco embrionárias, que têm a capacidade singular de colonizar todos os tecidos de um embrião hospedeiro, inclusive de sua linhagem germinal; 2) o desenvolvimento de métodos que permitem a recombinação homóloga entre um DNA que ''ingressa'' e sua seqüência cromossomal cognata (''mira'' genética - ''gene targetting'' Como resultado, tornou-se possível criar camundongos que carreiam mutações nulas em qualquer gene clonado (camundongos ''knock out''). Tal possibilidade revolucionou a abordagem genética de quase todos os aspectos da biologia do camundongo. Em anos recentes, o escopo da ''mira'' genética ampliou-se ainda mais devido ao refinamento da tecnologia de ''knock out'': outros tipos de modificações genéticas podem agora ser criadas, incluindo mutações sutis (mutações punctiformes, micro-deleções ou inserções, etc) e rearranjos cromossomais tais como grandes deleções, duplicações e translocações. Finalmente, têm sido implementados métodos que permitem a criação de mutações condicionais, permitindo o estudo da função gênica ao longo da vida do animal, quando a inativação do gene acarreta a letalidade embrionária. Neste artigo, apresentamos uma revisão geral dos métodos e situações usadas para a modificação programada do genoma do camundongo e acentuamos seu enorme interesse para o estudo da biologia dos mamíferos.